PERBANDINGAN EKOSISTEM MUSLIM-FRIENDLY TRAVEL INDONESIA, MALAYSIA, DAN ARAB SAUDI BERDASARKAN STATE OF THE GLOBAL ISLAMIC ECONOMY REPORT 2024/25 - Rizky Fauzi, Abiseka Sahal; Ramandini, Nurul (Taksasila Edukasi Insani, 2026)
The growth of the global Muslim market is driving an increase in demand for halal tourism; the SGIE Report 2024/25 notes that Muslim outbound travel spending amounted to US 217 billion (2023) and is projected to reach US 384 billion by 2028 (CAGR 12.1%). This study aims to analyze Indonesia's position in Muslim-friendly travel, compare it with Malaysia and Saudi Arabia, and identify the drivers/barriers to ecosystem-based competitiveness. The analysis uses the Global Islamic Economy Indicator (GIEI) framework, which is a weighted composite index with 52 metrics in five dimensions (financial, regulatory, awareness, social, innovation). The methods used are literature study and comparative analysis of SGIE 2024/25 data and scientific references related to the concepts of halal tourism and Muslim-friendly tourism. The results show that Malaysia leads the Muslim-Friendly Travel sector (136.8), followed by Indonesia (102.4) and Saudi Arabia (91.1), which is in line with the 2024 GMTI, which ranks Indonesia and Malaysia at the top, while Saudi Arabia is in the next position. Malaysia's excellence is supported by policy integration, standardization/certification, and promotion; Saudi Arabia excels in religious demand and investment acceleration; while Indonesia is strong in destination potential, but needs to strengthen service standardization, global promotion, digital innovation, and ecosystem coordination to improve competitiveness.Keywords : SGIE, GIEI, pariwisata halal, Muslim-friendly tourism, Indonesia